Niealergiczny nieżyt nosa - Buczyłko, Krzysztof (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2009)
Non-allergic rhinitis (NAR) can be defined as a chronic nasal inflammation which is not caused by systemic IgE-dependent mechanisms. Non-allergic rhinitis is common and probably affects far more than 200 million people worldwide, both children and adults. Asthma was more frequently associated with NAR than with AR. Non-allergic rhinitis was more frequently associated with older age, perennial symptoms and female gender. More NAR than AR patients also had drug allergy, pharyngitis, sinusitis (CRS) and urticaria. Chronic rhinosinusitis was not significantly different in allergic and non-allergic patients. Nasal polyps were found equally in both groups. Ten genes were found to be of pathophysiological interest for non- infectious non-allergic rhinitis (NINAR) and of these, c-fos and Cdc42 seemed to be of specific interest, although the role of c-fos and Cdc42 in upper airway inflammation remains unknown. Four main types of inflammatory NAR have been defined: NAR infiltrated by eosinophils (NARES), by mast cells (NARMA), by neutrophils (NARNE), and with infiltration by eosinophils and mast cells (NARESMA). NARESMA patients had the worst QoL. Patients with NAR generally experienced worsening disease, with an increase in the persistence and severity of nasal symptoms and new comorbidities over time. The most frequent comorbidities at the re-evaluation were asthma and conjunctivitis followed by CRS. Conjunctivitis and sinusitis were more prominent in the AR than NAR group. Autoimmune thyroid disease was found in 10% of the AR, 14% of the NAR and 9.9% of controls. No statistically significant association was noted. Intranasal antihistamine therapy represents an effective mode of drug delivery in patients with NAR and is an important option for therapy, particularly if rapid symptom relief is required or if congestion is a major symptom. Use of azelastine plus nasal corticosteroids is more effective in both AR and NAR, suggesting that this combination represents an effective treatment strategy for all patients.